Regeneration pattern and genome-wide transcription profile of rhizome axillary buds after perennial rice harvest - Yao, Fan; Hu, Qingyi; Yu, Yingzhen; Yang, Lifan; Jiao, Shuliang; Huang, Guangfu; Zhang, Shilai; Hu, Fengyi; Huang, Liyu (Frontiers in Plant Science, 2022)
Perennial rice is a new type of rice that allows the harvest of rice for multiple years without growing new seedlings annually. This technology represents a green and sustainable agricultural production mode with many advantages for balancing agricultural ecology and food security. However, the differences in regeneration patterns between perennial and annual rice and the gene regulatory pathways of the apical dominance in axillary bud growth after harvest in perennial rice are still unclear. In this study, perennial rice (PR23) and annual rice (Chugeng28) were used to investigate axillary bud growth patterns before and after apical spike removal. After elimination of apical dominance at different development stages, perennial rice rhizome axillary buds at the compression nodes germinated more rapidly than others and developed into new seedlings. The axillary buds at the high-position nodes in annual rice grew faster than those at other nodes. Furthermore, the global gene expression patterns of PR23 rhizome buds at compression nodes grown for 1, 3, 4, and 5 days after apical spike removal were analyzed by transcriptome sequencing. Compared with the control buds without apical removal, 264, 3,484, 2,095, and 3,398 genes were up-regulated, and 674, 3,484, 1,594, and 1,824 genes were down-regulated in the buds grown for 1, 3, 4, and 5 days after apical spike removal, respectively. Trend analysis of the expressed genes at different time points was performed and co-expression network was constructed to identify key genes in rhizome axillary bud regrowth. The results showed that 85 hub genes involved in 12 co-regulatory networks were mainly enriched in the light system, photosynthesis-antenna protein, plant hormone signal transduction, ABC transporter and metabolic pathways, which suggested that hormone and photosynthetic signals might play important roles in the regulation of rhizome axillary bud regeneration in perennial rice. Overall, this study clarified the differences in the regeneration patterns of axillary buds between perennial and annual rice and provided insight into the complex regulatory networks during the regeneration of rhizome axillary buds in perennial rice.